Strecker degradation of amino acids promoted by a camphor-derived sulfonamide - Carvalho, M. Fernanda N. N.; Ferreira, M. João; Knittel, Ana S. O.; Oliveira, Maria da Conceição; Costa Pessoa, João; Herrmann, Rudolf; Wagner, Gabriele (Beilstein Journal of Organic Chemistry, 2016)
A camphor-derived sulfonimine with a conjugated carbonyl group, oxoimine 1 (O2SNC10H13O), reacts with amino acids (glycine, L-alanine, L-phenylalanine, L-leucine) to form a compound O2SNC10H13NC10H14NSO2 (2) which was characterized by spectroscopic means (MS and NMR) and supported by DFT calculations. The product, a single diastereoisomer, contains two oxoimine units connected by a –N= bridge, and thus has a structural analogy to the colored product Ruhemann´s purple obtained by the ninhydrin reaction with amino acids. A plausible reaction mechanism that involves zwitterions, a Strecker degradation of an intermediate imine and water-catalyzed tautomerizations was developed by means of DFT calculations on potential transition states.
Keywords: amino acids; camphorsulfonylimine; DFT calculations; NMR characterization; Strecker degradation